Aksesibilitas Bagi Anak Berkebutuhan Khusus di SLB Negeri Sukoharjo - Prajalani, Yuniviana Nur Hari (Indonesian Journal of Disability Studies, 2017)
This study aims to determine and evaluate the availability of facilities and accessibility of buildings in the SLB Negeri Sukoharjo for children with special needs, especially blind and physical impairment. The research method used is a qualitative research. Data were collected by observation, documentation, and interview techniques. Data analysis using qualitative description by comparing data obtained from the field with the standard provisions according to the Minister of Public Works Decree Number 30 of 2006 which regulates the technical guidance of facilities and accessibility of buildings and the environment. The results showed that accessibility for the blind and physical impairment in SLB Negeri Sukoharjo less accessible. Therefore, there needs to be improvement efforts in some parts of the building of SLB Sukoharjo to make it more accessible for PwDs.